2013
DOI: 10.1159/000346785
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Schwannoma of the Cecum: Case Report and Review of the Literature

Abstract: A 78-year-old woman presented with an abdominal mass diagnosed by ultrasound and computed tomography. The patient underwent a laparotomy, during which a retroperitoneal tumor adherent to the cecum wall was identified. Microscopically, it showed spindle-cell proliferation in whorls, with low mitotic count (2 per 50 high-power fields) and was strongly positive for S-100 protein and vimentin. The final diagnosis was benign schwannoma of the cecum and no further treatment was required. Large intestine schwannomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…For differential diagnosis of schwannoma, abdominal CT scan can help differentiate between schwannoma and other mesenchymal tumors. Schwannomas appear as well-defined homogenous mural masses with low enhancement [ 1 , 5 , 7 , 10 , 11 , 14 , 35 , 36 , 40 , 51 , 70 ] in comparison with the heterogenous aspect of GIST and the ill-defined aspect of adenocarcinomas [ 72 ]. Less than half of the published case reports had a CT scan done, approximately half of these had endoluminal resection and did not require abdominal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For differential diagnosis of schwannoma, abdominal CT scan can help differentiate between schwannoma and other mesenchymal tumors. Schwannomas appear as well-defined homogenous mural masses with low enhancement [ 1 , 5 , 7 , 10 , 11 , 14 , 35 , 36 , 40 , 51 , 70 ] in comparison with the heterogenous aspect of GIST and the ill-defined aspect of adenocarcinomas [ 72 ]. Less than half of the published case reports had a CT scan done, approximately half of these had endoluminal resection and did not require abdominal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas are extremely rare tumours of nerve sheaths, developing from Schwann cells. In the GI tract, they present as spindle cell tumours and account for approximately 2–6% of all mesenchymal tumours [1].…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas of the gastrointestinal tract are spindle cell tumours that originate from peripheral nerve lining Schwann cells. Outside the central nervous system it represents a rare entity, accounting for approximately 2–6% of all mesenchymal tumours [1]. As it normally arises from intracranial nerves and spinal nerves, neurosurgeons encounter the bulk of these cases, however surgeons, radiologists, gastroenterologists and histopathologists are occasionally consulted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that perilesional lymphadenopathy are more often observed in gastric schwannomas than in gastric GIST (7). Although it is not certain, these lymph nodes are presumed to be reactive hyperplasia due to the fact that There are fourteen case reports of colonic schwannomas written in English or Korean and these reports provide accessible information about imaging findings (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We reviewed these cases as well as ours ( Table 1).…”
Section: Isolated Colonic Schwannoma In the Ascendingmentioning
confidence: 99%